A comparison of recent models for fatigue crack tip deformation. (October 2019) - Nowell, D.; Nowell, S.C.
Highlights: Crack opening profiles, measured by DIC are used to capture elastic and plastic components of the crack tip field. The Pommier and Hamam and the CJP model are shown to have a similar modification for crack tip plasticity. We show that the crack tip field is similar to that reported in the literature. Abstract: Fatigue crack propagation occupies much of the life of engineering components, particularly in the short crack regime. It is important to understand the mechanisms of propagation in order to carry out damage tolerance assessment and to predict component service life. The paper describes experiments carried out at macro- and micro-scale using digital image correlation to measure near-tip displacements. From these, various key parameters governing crack growth are extracted, and different models of fatigue crack deformation are validated. In particular, it is concluded that the Pommier and Hamam and the CJP models for fatigue crack displacement and stress fields have rather similar approaches to capturing the effects of crack tip plasticity.